Classification and race characteristics of all-time best male 800m runners - Gyimes, Z.; Kelemen, B.; Kovács, B. (Scientific Journal of Sport and Performance, 2025)
Purpose: The aim of the study was to investigate all-time 80 best male 800m runners` fastest ever 800m races in tactical aspect.